Coping mechanisms in Education in the face of the COVID-19: Adoption of technologies, psychological impacts, and new teaching-learning paradigms - de Cássia Rondina, Regina [UNESP]; da Silva, Rafaela Carolina [UNESP]; Ramos, Sonia Maria Petitto [UNESP]; Zocarato, Clayton Alexandre (Universidade Estadual de Maringa, 2021)
This research addresses the challenges faced by teachers and students as a consequence of the COVID-19 pandemic, highlighting the psychological impact associated with the sudden need to adopt digital teaching tools in everyday school life. Studies of this nature are necessary to support preventive and/or therapeutic actions aimed at coping with emerging changes. Therefore, we intended to understand the current scenario of distance education and how it interferes in the mental health of teachers and students, in such a way as to enable them to deal with this new context, which tends to remain active beyond this pandemic. We performed a survey of publications in the Web of Science and Google Scholar databases. Thus, we found and analyzed eight field studies on the topic. The main difficulties reported by research participants refer to problems related to the adaptability of computer programs, the adaptation of teaching strategies to the digital model and the need to teach, simultaneously, distance and face-to-face synchronous classes. We found reports of exhaustion, anxiety, stress and fear due to the possibility of job loss and/or exposure to the virus, besides overload of work. As a gap in the literature, we noted an absence of studies on the topic involving teachers and students of elementary and high school in Brazil and abroad. Keywords: remote education; educational technology; schooling; teaching-learning.
Mecanismos de afrontamiento (coping) en Educación ante el COVID-19: Adopción de tecnologías, impactos psicológicos y nuevos paradigmas de enseñanza-aprendizaje
Mecanismos de enfrentamento (coping) na Educação ante a pandemia de COVID-19: Adoção de tecnologias, impactos psicológicos e novos paradigmas ensino-aprendizagem
Keywords: educational technology; remote education; schooling; teaching-learning